Premarital Counseling and Scale in Madinah - Jeledan, Tagreed Malik Yousif (Journal of Educational and Psychological Sciences, 2020)
The study aims to build a standardized Premarital scale to identify the personality, social, economic, and physical characteristics of the future couples, with the aim of providing a premarital counseling service in a manner that is appropriate for them and find out the psychometric properties of it. The study followed the descriptive analytical method. The scale was applied to a sample of (100) hundred individuals (45 males and 55 females) who were randomly selected. The sample age ranged from 15 to 50 years. The results of the study found that the "premarital scale" that was built has good psychometric properties in terms of validity and consistency necessary to apply it to those who are going to marry in Medina, in order to provide a "premarital counseling" service for them that is appropriate to their personality traits, social, economic, and physical characteristics. The study presented a set of recommendations, among them was to do further studies aimed at verifying the validity and reliability of the scale on different environments and societies.
Keywords: Pre- marital counseling; Premarital Scale; psychometric properties of the premarital scale